Analysis of the Use of Artificial Intelligence (AI) in Learning Development Assessments Based on the Seven Characters at Undhira - Christian Tonyjanto; Dermawan Waruwu; Putu Andyka Putra Gotama; I Putu Pranatha Sentosa (Proceeding of the International Conference on Global Education and Learning, 2024)
The research was conducted to find out how artificial intelligence (AI) technology can be used to evaluate the development of seven characters in Undhira students. The seven characters in question are Integrity, Self-Confidence, Diversity, Entrepreneurship, Professionalism, Servant Leaders, Global Insight. In the research conducted, the main variables were learning motivation and the use of artificial intelligence designed by prioritizing the seven Undhira characters. The analysis obtained was that the artificial intelligence used for learning assessment obtained the following analysis: 1) arousing interest, 2) determining common goals, 3) building self-confidence, and 4) creating a positive learning environment.